A systematic review of the clinical effectiveness of aloe vera for the prevention and treatment of chronic wounds - Ahmad Nur Afieq Idrus,; Rehman, Khurram; Mohd Hanif Zulfakar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Aloe vera is an herbaceous and perennial plant that belongs to the Liliaceae family and used for many medicinal purposes. Aloe vera have been associated with the treatment of skin burns and postoperative wound healing but not many clinical studies have been conducted to evaluate its effectiveness against chronic wounds such as pressure injury. The present study aimed to systematically review clinical trials investigating the effect of Aloe vera on the prevention and healing of chronic wounds. To identify all related published studies, Science Direct, Google Scholar, PubMed, and Ovid MEDLINE databases were searched in English language from the year 2015-2022. All clinical trials using Aloe vera gel, cream, or derivatives that included a control group with placebo or comparison with other treatments were included in the study according to the PRISMA selection process. In total, 11 trials that met the inclusion criteria were reviewed. The results of the studies showed successful use of Aloe vera in the prevention and treatment of chronic wounds including pressure injuries, chronic wound ulcers, diabetic foot ulcers, chronic anal fissures, and traumatic oral ulceration due to orthodontic appliances. Based on its safety and efficacy profile, this review concluded that Aloe vera has potential benefits to be used as a complementary or alternative treatment in chronic wounds along with conventional methods. Its ability to retain skin moisture and preservation of skin integrity supports its use in the prevention of ulcers.